Geology, Mineralogy and Geochemistry of the Late Cenozoic McMurdo Volcanic Group, Victoria Land, Antarctica - Kyle, Philip Raymond (11658268) (1976)
Rocks of the McMurdo Volcanic Group occur as stratovolcanoes, shield volcanoes, scoria cones, plugs, flows and volcanic piles up to 4000 m high along the Ross Sea margin of the Transantarctic Mountains and make up the Balleny Islands 300 km north of the Antarctic continental margin. The rocks are predominantly undersaturated and range from alkali basalt and basanite to trachyte and phonolite. Four volcanic provinces are recognised; Balleny, Hallett, Melbourne and Erebus. The Balleny volcanic province is situated along a transform fault in the South Pacific Ocean. The rocks are predominantly basanite. Hallett volcanic province occurs along the coast of northern Victoria Land as four elongate piles formed extensive of hyaloclastites, tuffs, breccias and capped by subaerial eruptive products. The lavas are a basanite/alkali basalt-trachyte-quartz trachyte association, and were extruded over the last 7 m.y. Melbourne volcanic province stretches across the Transantarctic Mountains in northern Victoria Land and ranges in age from 0 to 7 m.y. A Central Suite of intermediate and trachytic lavas form stratovolcanoes, cones and plugs, while many small basanite outcrops constitute a Local Suite. Three lava lineages, resulting from differentiation, are recognised. 1) Lavas at The Pleiades and Mt Overlord consist of a mildly potassic trachyandesite-tristanite-K-trachyte-peralkaline K-trachyte lineage. Major, trace and rare earth element (REE) data suggest evolution by fractional crystallization of olivine, clinopyroxene, magnetite, apatite and feldspar. 2) A basanite-nepheline hawaiite-nepheline mugearite-nepheline benmoreite lineage, found at The Pleiades is believed to result from fractional crystallization of olivine, clinopyroxene, kaersutite, magnetite, apatite and feldspar. 3) An oversaturated (Q = 0 to 18%) strongly potassic quartz trachyandesite-quartz tristanite-quartz trachyte lineage occurs at only Mt Melbourne. The Erebus volcanic province covers all McMurdo Volcanic Group rocks in south Victoria Land. Mt Erebus itself is still active, but the province includes rocks as old as 15 m.y. Two lava lineages very similar chemically are recognised: 1) The Erebus lineage consists of strongly porphyritic nepheline hawaiite-nepheline benmoreite-anorthoclase phonolite. Phenocrysts of feldspar, clinopyroxene, olivine, magnetite and apatite are characteristic. The chemistry of the lineage is compatible with fractional crystallization of the phenocryst phases. 2) A kaersutite lineage consists of basanite-nepheline hawaiite-nepheline mugearite-nepheline benmoreite-kaersutite phonolite-pyroxene phonolite. Clinopyroxene (Wo44-48 En40-48 Fs7-14) is ubiquitous, kaersutite is common in all intermediate lavas and primary olivine (Fa12 to Fa26) is confined to the basanites. Major element mass balance models for lavas from Hut Point Peninsula suggest formation by fractional crystallization of olivine, clinopyroxene, spinel (includes magnetite and ilmenite), kaersutite, feldspar and apatite. Middle REE show a marked depletion consistent with kaersutite fractionation. REE abundances were evaluated using the mass balance models and published partition coefficients. Calculated REE abundances show excellent agreement with the measured values. Abundances of "incompatible" elements Pb, Rb, Cs, Th and U are not consistent with the models and "volatile enrichment" processes are invoked to explain their abundances. Intermediate lavas of the kaersutite lineage are rare in the Erebus volcanic province, occurring only at Hut Point Peninsula and Brown Peninsula. At other areas basanite and phonolite lavas predominate. However these are considered to form by fractional crystallization processes similar to Hut Point Peninsula lavas. Erebus lineage lavas differentiated at higher temperatures and, lower PH2O than those of the kaersutite lineage, which characterize the periphery of Ross Island. REE abundances and comparison with experimental melting studies indicate DVDP basanite originated by a low degree of partial melting (1-5%) of a hydrous garnet peridotite mantle at pressures of 25-30 kbars. These data suggest that Ross Island is the site of a mantle plume with a diameter of, about 100 km and centred on Mt Erebus.